Topological defects in silicene - Kosarev, Igor V. (2023)
Using the molecular dynamic simulations a new class of topological defects in silicene is investigated. Si atoms in silicene belong to two triangular sublattices shifted one with respect to the other by h along the direction normal to the sheet. Silicene can have two energetically equivalent structures when the first or second sublattice is above the other. Topological defects appear at the junctions of the domains of these two structures. Domain walls can be rectilinear or curvilinear. Such defects cannot disappear from the structure except as a result of the annihilation of defects with positive and negative topological charges. Structure and energy of the topological defects are calculated. The effect of temperature is shown. Similar defects inevitably exist in other group IVA elemental 2D materials with buckled structure, such as germanene, stanene, and plumbene. As a result of the work, the problem of experimental detection of such defects and the question of how they affect the physicochemical and mechanical properties of materials, in particular, toxicity or sensory properties, is posed.